Korelasi antara Beberapa Karakter Reproduksi dengan Panjang Total Ikan Brek [Puntius orphoides (Valenciennes 1842)] di Sungai Klawing Purbalingga - Suhestri Suryaningsih; Mammed Sagi; Kamiso Handoyo Nitimulyo; Suwarno Hadisusanto (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
The red chick barb [Puntius orphoides (Valenciennes 1842)] is a member of Cyprinidae with high economic value. However, this species is still uncultured. The high market demand is fulfilled by direct collection  from their natural habitat.  In order to avoid overexploitation, domestication effort is needed.  The success of this effort needs some biological information e.g. reproductive characters.  This research aims to know some reproductive characters of red cheek barb collected at Klawing River Purbalingga Central Java.  A survey method was used with performing simple random sampling technique. The measured parameters were gonad maturity, fecundity, and gonad somatic indices (GSI) related to total length. The fish were collected monthly from June until November 2009. Data analysis includes length distribution, and correlation among gonad maturity, fecundity, and gonad somatic indices with body length. The result showed that red cheek barb from Klawing River has variable body length, most of the female individuals (34.37%) had body length ranges from 14.3-16.2 cm, whereas the majority of the male individuals (44.95%) had length distribution from 12.1-14.6 cm. The variation on  gonad maturity was observed during the research both on female and male individuals. However, most of the populations were on the highest level of gonad maturity (level IV) only in September and October. A positive correlation between gonad maturity and body length was observed on the male individuals (r=0.0424) as well as on the female individuals (r=0.4339). The fecundity was ranges from 4.097 up to 32.794 eggs. A positive correlation was also observed between fecundity and body length (r=0.6403). A monthly GSI variation was found both on the female and the male individuals with the highest peak of GSI was observed in September and October. A positive correlation between GSI and body length was found on female individuals (r=7.07 x 10-3) as well as on male individuals (r=0.376).